(untitled) (International Journal of Innovative Technologies in Economy, 2025)
In today’s multicultural and varied educational environment, culturally responsive teaching (CRT) is a crucial learner-centered approach. Creating inclusive learning communities, overcoming cultural barriers, and taking into account a variety of learning styles, it promotes and improves learners’ educational experiences. Nevertheless, little research has shown how CRT affects economics instruction. Through a thorough evaluation of the literature, this study sought to close this gap. Data was gathered from 55 academic, peer-reviewed publications that examined CRT as a teaching method for economics classes and were published between 2020 and 2024. Data was analyzed using the thematic content analysis approach, and findings were theorized following asset-based pedagogy (ABP). Four themes for incorporating CRT into economics instruction were identified by the study. These strategies include using culturally responsive teaching materials and resources, encouraging learner-centered learning and discussion, integrating diverse cultural perspectives and experiences into economics curricula, and fostering collaboration between schools and community members, including indigenous knowledge holders. The study highlights the need for educators to recognize and value students’ cultural backgrounds, contributing to fresh insights in the integration of CRT in economics education.